Cost Effectiveness of First-Line Treatment with Doxorubicin/Ifosfamide Compared to Trabectedin Monotherapy in the Management of Advanced Soft Tissue Sarcoma in Italy, Spain, and Sweden. (2nd November 2013) - Guest, Julian F.; Panca, Monica; Sladkevicius, Erikas; Gough, Nicholas; Linch, Mark
Abstract : Background . Doxorubicin/ifosfamide is a first-line systemic chemotherapy for the majority of advanced soft tissue sarcoma (ASTS) subtypes. Trabectedin is indicated for the treatment of ASTS after failure of anthracyclines and/or ifosfamide; however it is being increasingly used off-label as a first-line treatment. This study estimated the cost effectiveness of these two treatments in the first-line management of ASTS in Italy, Spain, and Sweden. Methods . A Markov model was constructed to estimate the cost effectiveness of doxorubicin/ifosfamide compared to trabectedin monotherapy, defined as the cost per QALY gained, in each country. Results . First-line treatment with doxorubicin/ifosfamide resulted in lower two-year healthcare costs and more QALYs than first-line treatment with trabectedin monotherapy in all three countries. Probabilistic sensitivity analysis showed that at a cost per QALY threshold of €35, 000, >90% of a cohort would be cost effectively treated with doxorubicin/ifosfamide compared to trabectedin monotherapy in all three countries. Conclusion . Within the model's limitations, first-line treatment of patients with ASTS with doxorubicin/ifosfamide instead of trabectedin monotherapy affords a cost-effective use of publicly funded healthcare resources in Italy, Spain, and Sweden and is therefore the preferred treatment in all three countries. These findings support the recommendation that trabectedin should remain a second-line treatment.